Evaluation of the Usability of the Tiger Full-Foot Three-Dimensional Scanner for the Measurements of Basic Foot Dimensions in Clinical Practice - Laštovička, Ondřej; Cuberek, Roman; Janura, Miroslav; Klein, Tomáš (Journal of the American Podiatric Medical Association, 2022)
BACKGROUND: Foot dimension information is important both for footwear design and clinical applications. In recent years, noncontact three-dimensional (3-D) foot digitizers/scanners have become popular because they are noninvasive and are valid and reliable for most of the measures. Some of them also offer automated calculations of basic foot dimensions. We aimed to determine test-retest reliability, objectivity, and concurrent validity of the Tiger full-foot 3-D scanner and the relationship between manual measures of the medial longitudinal arch of the foot and alternative parameters obtained automatically by the scanner. METHODS: Intraclass correlation coefficients and minimal detectable change values were used to assess the reliability and objectivity of the scanner. Concurrent validity and the relationships between the arch height measures were determined by the Pearson correlation coefficient and the limits of agreement between the scanner and the caliper method. RESULTS: The relative and absolute agreement between the repeated measurements obtained by the scanner show excellent reliability and objectivity of linear measures and only good to nearly good test-retest reliability and objectivity of arch height. Correlations between the values obtained by the scanner and the caliper were generally higher in linear measures (rp ≥ 0.929). The representativeness of state of bony architecture by the soft-tissue margin of the medial foot arch demonstrates the lowest correlation among the measurements (rp ≤ 0.526). CONCLUSIONS: The Tiger full-foot 3-D scanner offers excellent reliability and objectivity in linear measures, which correspond to those obtained by the caliper method. However, values obtained by both methods should not be used interchangeably. The arch height measure is less accurate, which could limit its use in some clinical applications. Orthotists and related professions probably appreciate the scanner more than other specialists.
Keywords: tělesná výška; Body Height; Foot; Reproducibility of Results; noha (od hlezna dolů); lidé; reprodukovatelnost výsledků; dolní končetina; Lower Extremity; Humans